2020
DOI: 10.14710/jitaa.45.2.115-123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different transportation period on body weight loss, hematological and biochemical stress responses of sheep

Abstract: The study was conducted to evaluate the duration of road transportation during 4, 8 and 12 hours on body weight loss, hematological and biochemical responses of sheep. Twenty-four male Javanese thin tailed sheep were separated into transported group (T4, T8 and T12) and non-transported group (NT4, NT8 and NT12). Transportation (T) groups were transported for 4, 8 and 12 h in the same open pick up with 0.28 m2/head of loading density. Body weight, haematological and biochemical blood profiles were determined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Changes in biochemical and hormonal profiles are physiological responses of livestock to adapt to different climatic conditions so that they can survive and maintain productivity under changing climates (Maurya et al 2015). The physiological profile of several hormones, including thyroxine, cortisol, and testosterone, are affected by the prevailing environmental conditions (Hilal and AL-Saeed 2020;Lendrawati et al 2020;Perumal et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in biochemical and hormonal profiles are physiological responses of livestock to adapt to different climatic conditions so that they can survive and maintain productivity under changing climates (Maurya et al 2015). The physiological profile of several hormones, including thyroxine, cortisol, and testosterone, are affected by the prevailing environmental conditions (Hilal and AL-Saeed 2020;Lendrawati et al 2020;Perumal et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary study in Indonesia 1114 (2022) 012085 IOP Publishing doi:10.1088/1755-1315/1114/1/012085 2 conducted by Baihaqi et al [5] on the transportation of sheep concluded that the loss of body weight of livestock at a transportation time of 20 hours of travel reached 11.59 ± 2.75 percent of the initial weight. Some study conducted to minimize the negative effect of transportation, such as supplementation of vitamin C [6], electrolyte [7], Se-Met and Cr-Met [8] and molasses [9].…”
Section: Introductionmentioning
confidence: 99%